Is Class Inequality Reproduced in Sofia’s High Schools? Evidence from Data on Sofia’s High Schools - Rusinov, Stoycho (Педагогически форум, 2025)
This study examines the social efficiency of elitised secondary education in Sofia. The focus is on the reproduction of class inequality in the context of the sociology of education. Data from the Bulgarian educational system is used, specifically the minimum admission scores, which are calculated as a combination of the results from the 7th-grade exams for each school, and the school performance on the 12th-grade Bulgarian language and literature matriculation exam, to investigate the relationship between students' socio-economic background and their achievements. The results indicate that the minimum admission score from 7th grade, five years earlier, significantly correlates with matriculation exam performance, highlighting the system's inefficiency in overcoming class differences and educational inequalities. The study offers a comparative analysis with the educational systems of Germany, Austria, and France, emphasizing the need for reforms in the Bulgarian context.